IMPLIKASI PERILAKU TIDAK ETIS DALAM BISNIS: LITERATURE REVIEW - Akmal Aldino Amien; Iriani Ismail (JURNAL LENTERA BISNIS, 2023)
This research is a literature review that presents a holistic picture of the impact of unethical behavior in a business context. The impact of unethical behavior includes implications for companies, employees, consumers and society in general. This literature review analyzes the consequences of unethical actions, explores ethical frameworks that can assist in addressing unethical behavior, and presents relevant business ethics principles and ethical theories. Professional ethics, business law, and the development of business ethics theory are also the focus of this research. Apart from that, this research also covers other topics such as ethical leadership, transparency practices, accountability, and implementing clear policies in business. Literature studies show that business ethics plays an important role in overcoming unethical behavior such as corruption, discrimination, and neglect of environmental protection. Apart from that, this research also covers the application of artificial intelligence in information systems, the challenges of non-utilitarian ethics, as well as an analysis of challenges and opportunities in the development of economic globalization in business law in Indonesia. Keywords: Business ethics, leaders, employees.